Proyecto de factibilidad para la producción y comercialización de chocolate artesanal en la ciudad de Santo Domingo, provincia Santo Domingo de los Tsáchilas - Bravo Jiménez, Dayana Belén (2024)
The economy of the city of Santo Domingo de los Tsáchilas has potential, but the lack of investment limits its growth. This project offers an alternative to the cocoa sector through the creation of a new company in the area. This alternative shows the feasibility of marketing artisanal chocolate manufactured from cocoa local plantations. In this way, the cost of cocoa as the main raw material would be much lower since it would not be necessary to use intermediaries to obtain it. Based on this research process, the general objective was set as follows: To elaborate the feasibility project for the production and commercialization of artisan chocolate in the city of Santo Domingo. We analyzed the preference of the approximately 96151 families in the city to consume the product for its health benefits and its more affordable price. In addition, there is no local company that can meet the existing demand. After conducting a statistical evaluation with the results obtained through surveys, interviews and direct observation, it was determined that there is an unsatisfied demand of 24645 Kg for artisanal chocolate, representing a real business opportunity. The positive indicators obtained, Net Present Value (VAN=9140,51) and the Interest Rate of Return (TIR=17,26) proved the feasibility of creating the company for the production and commercialization of artisan chocolate bars.